Effect of CYP2C19 and ABCB1 single nucleotide polymorphisms on outcomes of treatment with ticagrelor versus clopidogrel for acute coronary syndromes: a genetic substudy of the PLATO trial - Wallentin, Lars; James, Stefan; Storey, Robert F; Armstrong, Martin; Barratt, Bryan J; Horrow, Jay; Husted, Steen; Katus, Hugo; Steg, P Gabriel; Shah, Svati H; Becker, Richard C (The lancet, 2010)
In the PLATO trial of ticagrelor versus clopidogrel for treatment of acute coronary syndromes, ticagrelor reduced the composite outcome of cardiovascular death, myocardial infarction, and stroke, but increased events of major bleeding related to non-coronary artery bypass graft (CABG). CYP2C19 and ABCB1 genotypes are known to influence the effects of clopidogrel. In this substudy, we investigated the effects of these genotypes on outcomes between and within treatment groups.